Add Yours: Millennial and Gen Z Cyberactivism on Instagram for #AllEyesOnRafah - Ferra Martian; Nabilla Anasty Fahzaria; Safina Arina Faza; Nazwaluna Camisha Zakaria (Ikatan Sarjana Komunikasi Indonesia, 2026)
Indonesia ranks fourth among Instagram users worldwide, with Generation Z and Millennials as dominant users. Instagram Stories, particularly the “Add Yours” feature, has become an important medium for self-expression and digital activism. The virality of the #AllEyesOnRafah campaign demonstrates how humanitarian issues can be expanded through simple digital participation mechanisms, while reflecting a shift in global solidarity to the visual and interactive realm. The objectives of this study include exploring the meaning of Palestine and genocide, the motives behind cyberactivism, and the typology of cyberactivism among Millennial and Generation Z Instagram users. This research uses a qualitative method with a cyber-phenomenological approach, which is constructed as an intrinsic case study in the Indonesian context to understand the experiences of Millennials and Gen Z in the campaign. Data were obtained through interviews with 15 informants, community observation, and a literature review. Analysis used the Color Coding Analysis Procedure (CCAP) to identify participating themes and motives. The findings indicate that for this generation, “Palestine” and “genocide” are interpreted as symbols of humanitarian crises and human rights violations. Motives for engagement primarily encourage empathy, moral obligation, a desire to raise awareness, and a sense of belonging in the digital community. The Add Yours feature facilitates a spectrum of interactions, from simple re-sharing to more powerful personal narratives. The findings of this study provide a theoretical contribution to the use of cyberphenomenology to understand the transition from symbolic to substantive digital advocacy, demonstrating how interactive features construct networked publics that demand global accountability.